FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Diah Ayu Sekar Astuti, Viriany (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about effects of profitability, leverage, asset structure, and activity to firm value of the sector manufacturing companies listed in the Indonesian stock exchange in the period of 2016-2018. The research is conducted by taking 73 samples using purposive sampling method. The result of this research that profitability and asset structure has a positive significant effect to firm value, activity has a negative significant effect to firm value, while liquidity and leverage has no significant effect to firm value.